2011
DOI: 10.1097/fbp.0b013e32834aff54
|View full text |Cite
|
Sign up to set email alerts
|

Some determinants of morphine effects on intracranial self-stimulation in rats

Abstract: Intracranial self-stimulation (ICSS) is one procedure used to evaluate abuse liability of drugs. The mu opioid receptor agonist morphine is an acknowledged drug of abuse, and the present study examined factors that may influence expression of abuse-related morphine effects on ICSS in rats. Adult male rats were equipped with intracranial electrodes targeting the medial forebrain bundle, and 10 stimulus frequencies (56-158 Hz in 0.05 log increments) were available during each daily session under a continuous rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
76
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 32 publications
17
76
2
Order By: Relevance
“…Morphine also blocked acidinduced depression of NAc DA and ICSS at a dose that had no significant effect on NAc DA or ICSS; however, mean DA levels were increased by morphine in this study, and previous microdialysis studies have reported that similar morphine doses produced significant increases in NAc DA (eg, see Cadoni and DiChiara, 2007). In addition, 3.2 mg/kg morphine can produce significant facilitation of ICSS depending on variables such as pretreatment time and history of opioid exposure (Altarifi and Negus, 2011). Accordingly, morphine blockade of acid effects on NAc DA and ICSS may reflect both reduced sensitivity to the noxious Figure 5 Pain-related modulation of PDYN and KOR mRNA expression levels in brain regions implicated in mood disorders as measured by qRT-PCR.…”
Section: Pain-related Depression Of Mesolimbic Da Releasecontrasting
confidence: 45%
See 2 more Smart Citations
“…Morphine also blocked acidinduced depression of NAc DA and ICSS at a dose that had no significant effect on NAc DA or ICSS; however, mean DA levels were increased by morphine in this study, and previous microdialysis studies have reported that similar morphine doses produced significant increases in NAc DA (eg, see Cadoni and DiChiara, 2007). In addition, 3.2 mg/kg morphine can produce significant facilitation of ICSS depending on variables such as pretreatment time and history of opioid exposure (Altarifi and Negus, 2011). Accordingly, morphine blockade of acid effects on NAc DA and ICSS may reflect both reduced sensitivity to the noxious Figure 5 Pain-related modulation of PDYN and KOR mRNA expression levels in brain regions implicated in mood disorders as measured by qRT-PCR.…”
Section: Pain-related Depression Of Mesolimbic Da Releasecontrasting
confidence: 45%
“…Training continued with presentation of three sequential components per day, and intensity was again adjusted as necessary until rats reliably responded for at least three and no more than six trials of all components for at least two consecutive days. Testing was conducted using drugs, doses, and pretreatment times identical to those used in microdialysis experiments, and as noted above, these parameters were based on previous studies from our laboratory (Altarifi and Negus, 2011;Negus et al, 2010bNegus et al, , 2012. ICSS test sessions consisted of seven sequential components.…”
Section: Assay Of Icssmentioning
confidence: 99%
See 1 more Smart Citation
“…These time-dependent effects in free-operant procedures highlighted the difficulty of dissociating abuse-related from motor effects in free-operant procedures and prompted subsequent studies with discrete-trial procedures in an effort to dissociate abuse-related and sedative effects; these studies found facilitation of ICSS even at early time points (Marcus and Kornetsky, 1974;Esposito and Kornetsky, 1977). More recent studies with frequencyrate procedures have confirmed that mu agonists produce complex effects on ICSS determined by factors that include dose, pretreatment time, and efficacy of the agonist at mu receptors (O 'Neill and Todtenkopf, 2010;Altarifi and Negus, 2011;Altarifi et al, 2012Altarifi et al, , 2013. For example, relatively high-efficacy mu agonists such as methadone, fentanyl, and morphine weakly facilitate ICSS at low doses; however, at higher doses, they produce initial ICSS depression followed later by ICSS facilitation.…”
Section: B Opioidsmentioning
confidence: 98%
“…As discussed above, depression of ICSS is a predominant effect of acute treatment with high-efficacy mu agonists like methadone, fentanyl, and morphine. However, repeated/chronic administration with morphine or other mu agonists produces tolerance to rate-decreasing effects and increased expression of abuse-related rate-increasing effects (Adams et al, 1972;Lorens and Mitchell, 1973;Koob et al, 1975;Carlezon and Wise, 1993a;Easterling and Holtzman, 1997a;Altarifi and Negus, 2011;Altarifi et al, 2012Altarifi et al, , 2013. It is especially relevant for abuse potential testing to note that, as with monoaminergic drugs discussed above, repeated treatment produces little or no tolerance to abuse-related ICSS facilitation by mu agonists.…”
Section: B Opioidsmentioning
confidence: 99%